Dream, Annie, dream - Brown, Waka T. (2022)
"In this empowering deconstruction of the so-called American Dream, a twelve-year-old Japanese American girl grapples with, and ultimately rises above, the racism and trials of middle school she experiences while chasing her dreams. As the daughter of immigrants who came to America for a better life, Annie Inoue was raised to dream big. And at the start of seventh grade, she's channeling that irrepressible hope into becoming the lead in her school play. So when Annie lands an impressive role in the production of The King and I, she's thrilled ... until she starts to hear grumbles from her mostly white classmates that she only got the part because it's an Asian play with Asian characters. Is this all people see when they see her? Is this the only kind of success they'll let her have -- one that they can tear down or use race to belittle? Disheartened but determined, Annie channels her hurt into a new dream: showing everyone what she's made of. Waka T. Brown, author of While I Was Away, delivers an uplifting coming-of-age story about a Japanese American girl's fight to make space for herself in a world that claims to celebrate everyone's differences but doesn't always follow through."--
Ages 8-12
Keywords: Middle school girls -- Juvenile fiction; Children's plays -- Juvenile fiction; Japanese Americans -- Juvenile fiction; Racism against Asians -- Juvenile fiction; Children of immigrants -- Juvenile fiction; Self-acceptance -- Juvenile fiction; Schools -- Juvenile fiction; Middle schools -- Juvenile fiction; Fiction; Juvenile works; Social problem fiction; Bildungsromans; Social problem fiction; Fiction; Romans